Chemically Prelithiated Hard‐Carbon Anode for High Power and High Capacity Li‐Ion Batteries. Issue 7 (28th January 2020) - Shen, Yifei; Qian, Jiangfeng; Yang, Hanxi; Zhong, Faping; Ai, Xinping
Abstract: Hard carbons (HC) have potential high capacities and power capability, prospectively serving as an alternative anode material for Li‐ion batteries (LIB). However, their low initial coulombic efficiency (ICE) and the resulting poor cyclability hinder their practical applications. Herein, a facile and effective approach is developed to prelithiate hard carbons by a spontaneous chemical reaction with lithium naphthalenide (Li‐Naph). Due to the mild reactivity and strong lithiation ability of Li‐Naph, HC anode can be prelithiated rapidly in a few minutes and controllably to a desirable level by tuning the reaction time. The as‐formed prelithiated hard carbon (pHC) has a thinner, denser, and more robust solid electrolyte interface layer consisting of uniformly distributed LiF, thus demonstrating a very high ICE, high power, and stable cyclability. When paired with the current commercial LiCoO2 and LiFePO4 cathodes, the assembled pHC/LiCoO2 and pHC/LiFePO4 full cells exhibit a high ICE of >95.0% and a nearly 100% utilization of electrode‐active materials, confirming a practical application of pHC for a new generation of high capacity and high power LIBs. Abstract : A facile chemical prelithiation approach is developed to eliminate the irreversible capacity loss of hard carbon (HC) anode via a spontaneous chemical reaction with lithium naphthalenide reagent. When paired with LiCoO2 cathode, the HC/LiCoO2 full cell demonstrates a high initial coulombic efficiency of >95.0%, confirming a practical application for high energy and high power Li‐ion batteries.